Preliminary Studies, Antimicrobial and Antioxidant Activity of Leaf, Stem Bark and Root Extracts of Calotropis Procera Plant - Njidari, Mathias; Kpesibe, Joseph F.; Shagal, Mohammed H. (African Journal of Biochemistry and Molecular Biology Research, 2024)
The phyto-components of leaf, root and Stembark of Calotropis procera L. Asclepiadaceae family species were screened by gas chromatography- mass spectroscopy (GC-MS) analysis. Ethanol extract was prepared by soxhlet apparatus from all the parts of C. procera. The present study aimed to determine the phytochemical screening, antimicrobial and anti-oxidant properties of the leaves, root and stem bark of the ethanol extracts of the C. procera plant. Phytochemical screening was carried out for all the three extracts obtained from the leaves, root and stem bark which revealed the presence of most secondary metabolites such as flavanol, phenol, alkaloids, saponins except glycosides in leaf, while alkaloids and saponins were absent in the root and glycosides absent in the stembark. From antibacterial result, the highest zone of inhibition of leave extract for E. coli was (14mm) and the lowest zone of inhibition was (2mm), the highest and lowest zone of inhibition for the leaf of Staph. A was (14mm and 4mm) respectively, Similarly, the highest zone of inhibition and the lowest zone of inhibition of leaves for Bacillus Cereus was (14mm) and (4mm). The highest zone of inhibition of Aspergillus favus was 12mm in the leaves extract and it was 14mm for Candida albicans in the leaves extract. The FTIR of F3 fraction of the leaf confirmed the presence of alkane, alkene, hydroxyl, amines and amides which showed characteristics peaks at 3326cm-1, 2945.07cm-1, 2833.56 cm-1, 1649.24 cm-1, 1449.04 cm-1, 1111.76 cm-1 and 1021cm-1..The chemical component of the ethanolic extracts of the leaves of C.procera as revealed by GC-MS consist of mainly twenty one (21) compounds ranging from phenol, Terpenes and fatty acids The ferric reducing antioxidant power assay (FRAP) was determined and the leaves and the root was observed to have higher antioxidant potential as the observance was 1.690 and 2.453nm for leaf and 2.44 concentration of 30 and 40 respectively. This study show that the leaves extract of C.procera inhibits bacterial and fungal growth and anti-oxidant properties which is very important for medicinal uses. The present investigation deals with the process of determining the phytocomponents, antioxidant and antibacterial active.